2022
DOI: 10.1101/2022.09.21.508688
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Massively-parallel Microbial mRNA Sequencing (M3-Seq) reveals heterogeneous behaviors in bacteria at single-cell resolution

Abstract: Bacterial populations are highly adaptive, enabling them to respond to and surviving in shifting environments or stresses. Yet, how these single-cell organisms vary and organize their behavior to tolerate stressors is poorly understood. This is because many bacterial subpopulations are rare and cannot be readily discovered by existing single-cell sequencing methods due to limitations in cell number and sequencing depth. Here we develop Massively-parallel Microbial mRNA sequencing (M3-Seq), which addresses thes… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…In addition, the use of blocking primers to deplete rRNA can potentially also be scaled down to single cells as we previously showed that EMBR-seq efficiently depletes rRNA from as little as 0.02 ng input total RNA ( 25 ). This corresponds to a pool of ~200 single bacteria (assuming ~0.1 pg of RNA per bacterial cell) and is in line with the sensitivity requirements of the existing methods that employ combinatorial barcoding strategies ( 49 , 51 , 56 , 57 ). Therefore, we anticipate that in the future EMBR-seq+ could potentially be applied to single cells, thereby adding to the growing toolkit for profiling individual bacterial cells.…”
Section: Discussionmentioning
confidence: 54%
“…In addition, the use of blocking primers to deplete rRNA can potentially also be scaled down to single cells as we previously showed that EMBR-seq efficiently depletes rRNA from as little as 0.02 ng input total RNA ( 25 ). This corresponds to a pool of ~200 single bacteria (assuming ~0.1 pg of RNA per bacterial cell) and is in line with the sensitivity requirements of the existing methods that employ combinatorial barcoding strategies ( 49 , 51 , 56 , 57 ). Therefore, we anticipate that in the future EMBR-seq+ could potentially be applied to single cells, thereby adding to the growing toolkit for profiling individual bacterial cells.…”
Section: Discussionmentioning
confidence: 54%
“…This work represents only an initial effort in this direction, but provides a foundational framework for genome-wide exploration of novel bacterial regulatory phenomena. As bacterial scRNA-seq methods evolve in scale, capture efficiency, and cost [61][62][63][64] , we predict that these methods, in combination with microscopy and molecular genetics approaches that allow mechanistic dissection of these phenomena, will illuminate a diverse ecosystem of dynamic transcriptional processes.…”
Section: Discussionmentioning
confidence: 99%